2012
DOI: 10.1016/j.bbrc.2012.04.116
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone and levonorgestrel regulate expression of 17βHSD-enzymes in progesterone receptor positive breast cancer cell line T47D

Abstract: The use of combined hormone replacement therapy (HRT) with oestrogens and progestins in postmenopausal women has been associated with an increased risk for developing breast cancer. The reasons are not fully understood, but influence of HRT on endogenous conversion of female sex hormones may be involved. The expression of 17 beta hydroxysteroid dehydrogenases (17βHSD), which are enzymes catalysing the conversion between more or less potent oestrogens, may partly be regulated by progestins. The breast cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…It has been reported that progestins, used as a treatment for endometriosis or included in hormone replacement therapy can influence the oxidative and reductive capacity of tissues, and medrogestone, 20-dihydro-dydrogesterone, and nomegestrol acetate all reduce HSD17B1 activity by 35-51% in cell lines tested [36, 55]. In the strongly progesterone receptor (PgR) positive breast cancer cell line T-47D, progesterone, levonorgestrel, and medroxyprogesterone acetate were shown to up-regulate HSD17B1 and HSD17B5 expression and down-regulate HSD17B2 expression, with smaller effects seen on HSD17B1 expression in the moderately positive MCF7 [79]. Recently the progestin Dienogest was shown to down-regulate both HSD17B1 and aromatase expression in endometriosis patients, if this is also applicable in breast cancer remains to be seen [80].…”
Section: Control Of Expression and Regulation Of Hsd17b1 And Hsd17b2mentioning
confidence: 99%
“…It has been reported that progestins, used as a treatment for endometriosis or included in hormone replacement therapy can influence the oxidative and reductive capacity of tissues, and medrogestone, 20-dihydro-dydrogesterone, and nomegestrol acetate all reduce HSD17B1 activity by 35-51% in cell lines tested [36, 55]. In the strongly progesterone receptor (PgR) positive breast cancer cell line T-47D, progesterone, levonorgestrel, and medroxyprogesterone acetate were shown to up-regulate HSD17B1 and HSD17B5 expression and down-regulate HSD17B2 expression, with smaller effects seen on HSD17B1 expression in the moderately positive MCF7 [79]. Recently the progestin Dienogest was shown to down-regulate both HSD17B1 and aromatase expression in endometriosis patients, if this is also applicable in breast cancer remains to be seen [80].…”
Section: Control Of Expression and Regulation Of Hsd17b1 And Hsd17b2mentioning
confidence: 99%
“…It is also important to notice that the MCF‐7 cell line used as positive control shows, in fact, an intermediate PR expression level in comparison with other human breast cancer cell lines such as T47D, which presents an approximately 20‐fold higher PR mRNA level . Therefore, the magnetoimmunosensor ability to clearly differentiate cells expressing an intermediate PR level highlights the potentiality of the developed methodology.…”
Section: Resultsmentioning
confidence: 89%
“…Some studies suggest that systemic progesterone treatment contributes to increased expression levels of reductive enzymes compared to oxidative ones, which results in a possible increase of estrogen hormones and thus increases the proliferation of breast epithelial cells. [11,12] In order to assess the cytotoxic impact of levonorgestrel silver nanoparticles and their liposomal systems on breast epithelial cells -MCF 10A, there were selected two concentrations 0.1 μM and 1 μM, respectively for 24 h. The data obtained revealed that at 0.1 μM no significant influence on cell viability was noted for 24 h (data not shown). At a concentration of 1 µM, there was a slight decrease in cell viability after treatment with Ag_NPs (viability ~93%), Lng_Ag_NPs (viability ~94%) and Lip_Ag_NPs (viability ~94%) (Fig.…”
Section: Resultsmentioning
confidence: 99%